Cosmology, Cosmologia, and Reality: How the Cosmological Model Challenges the Intelligibility of Reality - Benvenuti, Piero (2023)
More than four centuries after the Copernican Revolution and the consequent dismissal of Aristotelian Cosmology, the modern model of the cosmos has reached a similar if not superior level of a satisfactory understanding of physical reality. This extraordinary feat was achieved by using the Galilean scientific method of investigation, which was demonstrated to be extremely powerful in modeling cosmic physical phenomena. Unexpectedly, the main global characteristic of the cosmos was found to be its evolution in time; the universe’s history passes through very different phases, all linked together by a subtle fil rouge. This very fact, by now incontrovertible, is challenging our interpretation of reality by the sole use of the scientific method. The time may have come to reconnect, in a collaborative and constructive way, science, philosophy, and theology, which for too long have proceeded along independent, parallel, or even divergent paths. Only in this way may we hope to reach a more satisfactory understanding of global reality.
Keywords: Philosophy of nature; Scientific Method; Cosmology